Eksistensi Pasal 1320 KUHPerdata dalam Perjanjian Bisnis E-Commerce di Indonesia - Nurhayani Nurhayani; Ahmad Bardi; Sukran Jamil (CV. Ulil Albab Corp, 2024)
Business development is growing rapidly along with the development of information technology which has given birth to the term electronic commerce (e-commerce), namely digital business transactions both for the purpose of purchasing and selling products. Between business, information technology is also related to legal issues, namely contract law based on Article 1320 of the Civil Code which regulates the terms of an agreement, including agreement, competence, certain matters and halal causes. The problem that arises is whether Article 1320 of the Civil Code is still relevant as a legal basis for the practice of electronic commerce (e-commerce)? The research method used is a normative legal research method with a statutory approach and a conceptual approach. The research results show that Article 1320 of the Civil Code is open, so it is still relevant as a legal umbrella for e-commerce activities.